Efficient Stock Control Management System - Noorul Ahlami, Kamarul Zaman (2013)
This paper presents a pleasant automated system for stock management. Inventory system is important for industry to manage their things. The objectives of this paper are to help industry to manage inventory competently, improve performance and efficiency in handling inventory. Since the project will focus on small industry, the equipment used is not costly. The material used is software applications for keeping data and produce report of items and sale. Basically, the system will help user in key-in data using the items’ code. Then, the system will generate data based on function it is asked such as sales report and detect goods in and out of store. The system is user friendly and it is useful for newbie to become familiar with new system.